Uma abordagem integrativa para a delimitação das espécies Pachymenes ater de Saussure e Pachymenes ghilianii (Spinola) (Hymenoptera, Vespidae, Eumeninae) - Ferreira, Wellington Donizet (2018)
Integrative taxonomy is an approach in which different sources of evidence are used to solve taxonomic problems, including species delimitation. In this study, the principles of this approach were used to establish the specific limits of two species of solitary wasps (Hymenoptera, Vespidae, Eumeninae): Pachymenes ater de Saussure and Pachymenes ghilianii (Spinola). The geographic distribution of these two species, which overlaps for some extent, was used to estimate components of the ecological niche (climatic variables). A molecular study using sequences of mitochondrial DNA barcoding genes (COI and COII) was performed to test the reciprocal monophyly between P. ater and P. ghilianii. The revaluation of discrete morphological characters already established for both species was performed, as well as morphometric studies exploring continuous morphological characters. From 19 ecological variables it was not possible to establish the boundaries between these two species, with possible overlap of components of the ecological niche. The reciprocal monophyly between P. ater and P. ghilianii was recovered for the COI and COII sequences, using parsimony, maximum likelihood and Bayesian inference. The main morphological differences between P. ater and P. ghilianii are related to characters that can be observed in males, especially the genitalia and clypeus. Females of both species can be distinguished from differences in the extent of the pronotal carina. Continuous morphological characters were not informative enough for the practical distinction between the two species. From the fixed morphological characters and the reciprocal monophyly we recognize P. ater and P. ghilianii as distinct species.